Analisis Faktor – Faktor yang Mempengaruhi Kemiskinan di Kota Pasuruan - Zakia, Nur Aini; Muchtolifah (UNIVERSITAS NUSANTARA PGRI KEDIRI, 2022)
The goal of this investigation is to identify and investigate the factors that contribute to poverty in Pasuruan City. This study employs a quantitative approach, relying on secondary data from Central Statistics Agency publications spanning the years 2011 to 2020The analytical method was multiple linear regression analysis with IBM SPSS 25. Education has no effect on poverty, population has a negative and significant effect on poverty, and the unemployment rate has no effect on poverty, according to the findings. All variables, according to the findings, have an impact on poverty.